Developing Students' Critical Thinking Skills Through The Implementation of the Cambridge Curriculum - Mafaidah, Khil Miyatul Mafaidah; Mahfud, Muhammad; Umah, Faridatul (Universitas Terbuka, 2025)
This study aims to describe the implementation of the Cambridge international curriculum as a basis for developing students' critical thinking skills at Chalidana Islamic School, Gresik. The focus of the research is directed at the strategy of planning, implementation, and evaluation of learning that integrates the Cambridge curriculum with the national and Islamic curriculum. This research uses a qualitative approach with a case study method, through observation, interview, and documentation techniques, and data validation is done by triangulation and member check. The results show that curriculum implementation is systematic and contextual, emphasizing active learning and problem- based learning, with teachers developing structured lesson plans and attending regular training. Learning encourages student participation in discussions, presentations and reflections, while evaluation is done through formative, summative and Checkpoint Test assessments. There was significant improvement in students' critical thinking skills, although constraints were found in the use of English and teacher preparedness. Successful implementation was supported by school leadership, adequate facilities and a collaborative learning culture. The integration of Islamic values in the international curriculum helped strengthen students' character spiritually and intellectually. This study recommends improving teacher competence and English literacy programs as strategies to improve the implementation of the Cambridge curriculum.